C/EBPα binds and activates the PU.1 distal enhancer to induce monocyte lineage commitment - Yeamans, Christine (American Society of Hematology, 2007)
The PU.1 gene contains a 237–base pair distal enhancer located 14 kilobases upstream of its promoter. We have identified 2 sites within the PU.1 enhancer that strongly bind C/EBPα in a gel shift assay, and interaction with endogenous C/EBPα was confirmed by chromatin immunoprecipitation. Mutation of these DNA elements reduced activity of a distal enhancer-promoter construct 2- or 5-fold in a myeloid cell line, while mutation of a weaker C/EBPα-binding site located in the promoter minimally reduced activity in this context. These findings strengthen the link between C/EBPα and PU.1 expression. Reduction of C/EBPα activity in cases of acute myeloid leukemia may therefore contribute to transformation by reducing PU.1 levels. In addition, induction of PU.1 by C/EBPα during normal hematopoiesis may contribute to stem cell commitment to the myeloid lineages and further commitment to monopoiesis. Consistent with a requirement for C/EBPα induction of PU.1 during myeloid development, we demonstrate that C/EBPα induces monocytic development when expressed in PU.1(+/+), PU.1(+/−), or PU.1(+/kd) marrow myeloid progenitors but induces granulocyte lineage commitment in PU.1(kd/kd) cells lacking the PU.1 distal enhancer and does not induce either lineage in PU.1(−/−) cells.